Contagion effects of the subprime crisis in the European NYSE Euronext markets - Horta, Paulo (2018)
This paper presents three tests of contagion of theUS subprime crisis to the European stock markets of the NYSE Euronext group. Copula models are used to analyse dependence structures between the US and the other stock markets in the sample, in the pre-crisis and in the subprime crisis periods. The first test assesses the existence of contagion on the relevant stock markets’ indices, the second checks the homogeneity of contagion intensities, and the third compares contagion in financial and in industrial sectors’ indices. Results suggest that contagion exists, and is equally felt, in most stock markets and that investors anticipated a spreading of the financial crisis to the indices of industrial sectors, long before such dissemination was observable in the real economy.